Introduction to kinesiology studying physical activity - Brusseau, Timothy A. Jr; Knudson, Duane V. 1961- (Human Kinetics, 2022)
"Introduction to Kinesiology: Studying Physical Activity, Sixth Edition, gives students a complete overview of the field of kinesiology and explores the common career paths, questions, and ideas that are part of this discipline. The text stimulates curiosity about the field of kinesiology, gives insight into the subdisciplines of the field, and generates awareness of the current issues that kinesiology professionals seek to understand and solve"--